Beveridge Report (Pictorial charts with explanatory notes) - Beveridge, William Henry Beveridge, Baron, 1879-1963. Social insurance and allied services
1943-01 1943 1940s 14 pages : illustrations 2 Can we afford it? Can the nation afford the plan? Sir William Beveridge himself has given a terse answer to that - can we afford not to adopt his plan? Considered in the broadest terms of the present wastage of human material and wastage therefore of immense national potential, the Beveridge Plan is indeed the most economical measure in our financial history. In purely financial terms the actual cost to the Exchequer in the early years is low amounting to £351,000,000, as compared with an expenditure of £265,000,000 at the present rate, though it increases to £519,000,000 as the retirement pensions increase during the transition period. It is pertinent to remember that a country such as New Zealand, with far less resources proportionate to its population than Great Britain, is able to afford more generous provision for old age and widowhood than is envisaged by Sir William Beveridge. "As for those who say that all such projects are against the laws of political economy, and that in any event we shall be too poor after the war to afford the Beveridge Plan - they are talking nonsense. The astonishing thing about the Beveridge Plan is its cheapness, which is chiefly due to the fact that it is mainly an instrument for redistributing working-class incomes, rather than for making the rich pay for helping the poor. There is no question of our being unable to afford the Beveridge Plan, provided only that the aggregate of working-class incomes is kept sufficiently high. To keep it so is mainly a matter of keeping in regular employment everyone who can make a significant contribution to total output, even when that involves revising our notions of employability and of factory technique. Social security in effect pays for itself, on condition that total employment is kept at a high level. That is the essential point to keep in mind, and with it the certainty that full employment will not prevail if monopolists are allowed to set profit-mongering high and to reject as unemployable, a large fraction of the total post-war supply of workers." (New Statesman and Nation. 26.12.42.) The Economist (5.12.42) has expressed a similar view: "There is no doubt whatsoever that, if the national income is built up by the programmes which are perfectly practicable, and if the immense problems of world trade and British exports can be solved....... the minimum requirements of the Beveridge plan, which cannot very well be reduced, can be met." Will it give us too much? We may enquire if the scale of the benefits proposed is extravagant in relation to the needs of the recipients. The question is answered in the chart on 'Benefits and Subsistence Rates', and by Sir William Beveridge in his section on the cost of living, which shows that his benefits are based on the barest subsistance standards. If the argument of opponents of the Plan is valid that it is dangerous to reduce the margin between wages and benefits, then we are forced to the conclusion that a substantial proportion of the population must exist at some point below subsistence level as a permanent feature of our time. The real answer would appear to consist first in Sir William Beveridge's own stipulation that full employment will be maintained after the war, and secondly in the establishment of a minimum national wage, which, though not referred to in the Plan is its logical corollary. 126/TG/377/1/1/153